GNSS TEC-based detection and analysis of acoustic-gravity waves from the 2012 Sumatra double earthquake sequence - Srivastava, Sarthak (2021)
The Wharton Basin earthquake sequence on April 11, 2012, offshore Sumatra, represents the two largest (Mw > 8.0) strike-slip earthquakes ever recorded. Ground fault displacements generated a spectrum of acoustic-gravity waves due to solid Earth–atmosphere coupling. Wave-like perturbations in Total Electron Content (TEC) were therefore observed in ground-based Global Positioning System data. The waves arrive about 10 min after each earthquake and their spectral analysis reveals the presence of acoustic resonance frequencies of 3.8 and 4.4 mHz. The acoustic wave speeds of 0.9–1.2 km/s suggest coseismic ground movement as the primary wave generating mechanism instead of seismic Rayleigh waves. Gravity waves with frequencies below 2 mHz traveling with lower speeds of 0.21 km/s are also detected. Ray tracing using a simple numerical model traced the source of observed ionospheric perturbations to within 150 km distance of the epicenters. Large amplitude ionospheric disturbances were found to travel mostly in a north-south direction, an observation explained by the orientation of Earth’s geomagnetic field.